(untitled) (World Science, 2020)
The microwave field influence on the physicochemical properties of collagen and gelatin was studied. It is shown that when microwave field acts on the studied protein samples, a change in the molecules structure formation occurs. It was experimentally established that microwave exposure leads to the structural modification of collagen and gelatin molecules. This modification is accompanied by a change in the physicochemical properties of the studied biopolymers. It is shown that microwave field exposure leads to a decrease in the viscosity of collagen and gelatin solutions. A decrease in viscosity indicates that there’s a structural or transient processes occurring in protein molecules. The kinetics of swelling with time for collagen and gelatin samples was studied. It is shown that the use of a microwave field leads to a decrease in the rate constant of swelling. The swelling degree of the studied samples decreases on average by 60%. It is shown that isoelectric points of the proteins are shifted (pI from 5 to 6 for collagen and up to 5.5 for gelatin).